A review on the selected applications of forecasting models in renewable power systems. (February 2019) - Ahmed, Adil; Khalid, Muhammad
Abstract: This paper presents a literature review on the selected applications of renewable resource and power forecasting models to facilitate the optimal integration of renewable energy (RE) in power systems. This review is drafted on the basis of the selected high quality research publications from the past decade. Although the development of forecast models for RE generation, i.e., wind and solar energy, is a well-researched area, however, the performance of these models is usually evaluated using statistical error metrics. With regard to application, determining the optimality of accurate forecasts in terms of system economics and major planning aspects is an emerging phenomenon, that chalks out the main subject area of this survey. Specifically, the application domains include: 1) optimal power system dispatch (unit commitment, generation scheduling, economic dispatch), 2) optimal sizing of energy storage system, 3) energy market policies and profit maximization of market participants, 4) reliability assessment, and 5) optimal reserve size determination in power systems. The application-oriented review on these vital areas can be used by the power sector for familiarization with the recent trends and for analyzing the impact of forecasting improvement on optimal power system design and operation. Abstract : Highlights: An application-focused literature review on the role of forecasting models in renewable power system planning and operation. The study of forecasting in unit commitment, generation scheduling and economic dispatch problems. Investigation of the impact of forecasting uncertainties in energy market operations. Study of the application of forecasting in sizing problems, reserve estimation and power system reliability. The review is drafted on the basis of the high-quality research publications from the past decade.